2021
DOI: 10.24191/ajue.v17i3.14518
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate Students’ Perceived and Actual Performance in Critical Reading Skills

Abstract: The democratisation and commodification of education has witnessed an increase in postgraduate education as it is one of the main sources contributing to the advancement of knowledge, technology, and innovation. However, despite the significant rise in numbers, the returns at both the global and national      levels      have      been low due to high attrition and low completion rates among the students. One among the numerous factors cited has been the postgraduate students’ limited competencies in language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These results challenge some of the assumptions from previous research (Atkinson, 1997;Barnett, 2015;Khodary and AbdAllah, 2014;Shamida et al, 2021;Sundran et al, 2022;Ten Dam and Volman, 2004;Zin and Eng, 2014), indicating that engineering students in both Vietnam and Malaysia possess satisfactory critical reading skills. Particularly noteworthy was their proficiency in tackling higher level critical reading questions (Levels 5 and 6).…”
Section: Findings and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These results challenge some of the assumptions from previous research (Atkinson, 1997;Barnett, 2015;Khodary and AbdAllah, 2014;Shamida et al, 2021;Sundran et al, 2022;Ten Dam and Volman, 2004;Zin and Eng, 2014), indicating that engineering students in both Vietnam and Malaysia possess satisfactory critical reading skills. Particularly noteworthy was their proficiency in tackling higher level critical reading questions (Levels 5 and 6).…”
Section: Findings and Discussionsupporting
confidence: 68%
“…Developing such skills is pivotal for undergraduates, aiding comprehension, problem-solving, and constructive interaction with written material both within and beyond academia. However, studies highlight a deficiency in critical reading skills among Asian undergraduates, including Malaysians and Vietnamese, particularly in information analysis, evaluation, and synthesis (Abdullah and Suan, 2015; Khamkhong, 2018; Khodary and AbdAllah, 2014; Shamida et al, 2021; Zin and Eng, 2014; Zin et al, 2014). This skill gap is concerning for educational institutions, given its significance in academic achievement and real-world application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these three significant influences, critical reading proved to be the most important. Though similar findings were echoed by Shamida, Sidhu & Sofwah (2021) and Sidhu et al (2017), a contradictory finding was recorded by Muthukrishan et al (2022), where research skills were the determining factor in terms of influencing competencies in GOT. Nonetheless, critical reading is important as postgraduate students need to sieve through volumes of literature to identify the research gaps, and this can only be accomplished if they have developed a good grasp of current literature in their respective fields of study.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, the findings highlight the significance of research in this field of study that postgraduate students have minimal reading skills. Shamida et al (2021) found that postgraduate students' perceptions are much higher than their actual performance in academic reading skills, which has rarely been studied in ESL/EFL reading. Hence, scholars need to explore further and validate this research finding.…”
Section: Academic Reading Skillsmentioning
confidence: 93%